Near-Complete Genome Sequences of Nine SARS-CoV-2 Strains Harboring the D614G Mutation in Malaysia - Zainulabid, Ummu Afeera; Kamarudin, Norhidayah; Zulkifly, Ahmad Hafiz; Han, Ming Gan; Darren, Dean Tay; Shing, Wei Siew; Mat Yassim, Aini Syahida; Soffian, Sharmeen Nellisa; Mohd Fauzi, Ahmad Afif; Gazali, Ahmad Mahfuz; Maniam, Gaanty Pragas; Ahmad, Hajar Fauzan (2021)
Here, we report the nearly complete genome sequences of nine severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants with the D614G mutation. These viruses were detected from various infected individuals with different levels of severity from Pahang, Malaysia. In addition, this study described the presence of lineage B.1.351 as a type of variant of concern (VOC) and lineages B.1.466.2 and B.1.524 as local variants.